Viruses in the nucleus - Lucic, Bojana; Castro, Ines J. de; Lusic, Marina (Cold Spring Harbor perspectives in biology, 2021)
Viral infection is intrinsically linked to the capacity of the virus to generate progeny. Many DNA and some RNA viruses need to access the nuclear machinery and therefore transverse the nuclear envelope barrier through the nuclear pore complex. Viral genomes then become chromatinized either in their episomal form or upon integration into the host genome. Interactions with host DNA, transcription factors or nuclear bodies mediate their replication. Often interfering with nuclear functions, viruses use nuclear architecture to ensure persistent infections. Discovering these multiple modes of replication and persistence served in unraveling many important nuclear processes, such as nuclear trafficking, transcription, and splicing. Here, by using examples of DNA and RNA viral families, we portray the nucleus with the virus inside.
Gesehen am 15.10.2021